2014
DOI: 10.18632/oncotarget.2950
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the genetics of glioblastoma multiforme by familial exome sequencing

Abstract: Glioblastoma multiforme (GBM) is the most aggressive and malignant subtype of human brain tumors. While a family clustering of GBM has long been acknowledged, relevant hereditary factors still remained elusive. Exome sequencing of families offers the option to discover respective genetic factors.We sequenced blood samples of one of the rare affected families: while both parents were healthy, both children were diagnosed with GBM. We report 85 homozygous non-synonymous single nucleotide variations (SNVs) in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Compared to its family members, little is known about the function of PTPRB in the tumorigenesis process. A few recent studies have identified mutations in this gene in angiosarcoma, melanoma, GBM and more recently in premalignant colonic epithelial cells, suggestive of its potential role as a tumour suppressor in these cancer types . In our study, we investigated the potential tumour suppressive function of PTPRB in NSCLC by ectopically expressing this protein in A549 and H1299 cells, followed by tumorigenic assays.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared to its family members, little is known about the function of PTPRB in the tumorigenesis process. A few recent studies have identified mutations in this gene in angiosarcoma, melanoma, GBM and more recently in premalignant colonic epithelial cells, suggestive of its potential role as a tumour suppressor in these cancer types . In our study, we investigated the potential tumour suppressive function of PTPRB in NSCLC by ectopically expressing this protein in A549 and H1299 cells, followed by tumorigenic assays.…”
Section: Discussionmentioning
confidence: 97%
“…13 In addition, familial exome sequencing identified polymorphism of PTPRB gene in glioblastoma multiforme (GBM) individuals. 14 These observations suggest that PTPRB may function as a tumour suppressor in carcinogenesis and cancer development. However, it remains largely unknown whether mutations in this gene directly contribute to carcinogenesis in these cancer types.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further studies are warranted with increased sample sizes, to determine the role of CR1 in disease associations and pathogenesis mechanisms. [38] Malaria [36,37,40,42] Tuberculosis [46] Leprosy [47] rs17047661 (4841A>G) Sl1/Sl2 R1601G Sickle cell trait [38] Malaria [36,37,39,41,42,48] Tuberculosis [46] rs4844609 (4868T>A) Sl4/Sl5 T1610S Alzheimer disease [49][50][51][52] Cognitive decline [53,54] rs6691117 (4883A>G) KCAM +/-I1615V Erythrocyte Sedimentation Rate [55] Alzheimer Disease [56] Gastric cancer [57] Lung cancer [58] Glioblastoma multiforme [59]…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in DNA sequencing technology and associated bioinformatics enable the identification of novel predisposition genes . Early age of onset, syndromic features, multifocal primary tumors, associated primary immunodeficiency, and familial clustering are key features of hereditary susceptibility to cancer.…”
Section: Introductionmentioning
confidence: 99%